Pendidikan Inklusif Sebagai Gebrakan Solutif “Education for All” - Aris Armeth Daud Al Kahar (LPPM IAIN Sorong, 2019)
Educational for All Philosophy comes from a logical consequence of the statement that emphasized the need for an inclusive and non-discriminatory education. To accommodate different human diversity, an institution must be held to embrace the needs and desires of all parties, including children with special needs. Inclusive education is here to answer that challenge. The inclusive education approach in this case should not see this obstacle in terms of children or learners who have abnormalities, but must see these obstacles from their own education system, curriculum that is not suitable for them, inadequate facilities available, teachers who are not ready to serve them etc. Inclusive schools are not a school for students who have special needs but schools that provide effective services for all. In other words, inclusive education is education where all children are included, the needs of each child are accommodated or embraced and fulfilled not just tolerated